Upper-body power as measured by medicine-ball throw distance and its relationship to class level among 10- and 11-year-old female participants in club gymnastics - Salonia, M. A.; Chu, D. A.; Cheifetz, P. M.; Freidhoff, G. C. (The Journal of Strength and Conditioning Research, 2004)
The purpose of this study was to determine whether or not a relationship existed between upper-body power and class level among female club gymnasts. Sixty female gymnasts between the ages of 10 and 11 and between class levels 5 and 8 participated in the study. The distance of a medicine-ball throw was used to measure upper-body power. Three types of throws—overhead forward throw, overhead backward throw, and chest pass—were performed with a 6-lb rubber medicine ball. The mean distances of 2 trails were calculated and categorized into age group and class level. An analysis of variance design was used to determine the relationship between mean throw distances and throw type, age, and class level. Results: No significant differences were found between mean throw distances and throw type, age, or class level. The results of this study show no relationship between upper-body power of female gymnasts and throw type, age, and class level.